Pengembangan Dakwah di Masjid at-Taubah Desa Bojong Kecamatan Kemang Kabupaten Bogor - Ali Wahyudi, Suryadi; Hermansyah , Tantan; Fanshoby , Muhammad (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2025)
This study aims to analyze the development of da'wah activities at At-Taubah Mosque, located in Bojong Village, Bogor. Based on field observations, the number of worshipers at At-Taubah Mosque was previously not as large as it is today. Therefore, it is essential to understand the process of da'wah development in this mosque, which has shown significant progress over the past six years. This research employs a qualitative approach using field research methods. Primary data were obtained from the management of the At-Taubah Mosque Council (DKM), while secondary data were collected from the surrounding community. Data collection techniques included observation, interviews, and documentation. The findings reveal that the progress of da'wah development at At-Taubah Mosque is supported by various community programs, such as weekly study sessions for men and women, a qurban installment program, death contribution funds, assistance for the sick, and the use of the mosque as a venue for communal prayers. Additionally, the DKM At-Taubah strengthens social engagement by organizing activities like communal breakfast with worshipers. As an innovation in da'wah, the weekly study session results have also been published on social media platforms, particularly YouTube. Keyword: Strategy, Da'wah, Mosque, Communication, Da'wah Innovation